Pirfenidone-induced Eosinophilic Pleurisy - Hase, Isano (Intern Med, 2017)
The patient was a 69-year-old man with idiopathic pulmonary fibrosis who was taking pirfenidone. After 7 weeks of treatment, he suffered from left-sided eosinophilic pleurisy. Medical thoracoscopy was performed and the histopathological examination of the parietal pleura revealed the massive infiltration of eosinophils and lymphoid follicles. After stopping pirfenidone therapy, the patient's pleural effusion disappeared without additional treatment, and never recurred. This is the first case report of pirfenidone-induced pleurisy.